Respostas
respondido por:
1
60 ÷ {2. [-7+18 ÷ (-3+12)]} =
↓
60 ÷ {2 . [-7 + 18 ÷ 9]} =
↓
60 ÷ {2. [-7 + 2 ]} =
↓
60 ÷ {2. (-5) ]} =
↓
60 ÷ (-10) = -6
↓
60 ÷ {2 . [-7 + 18 ÷ 9]} =
↓
60 ÷ {2. [-7 + 2 ]} =
↓
60 ÷ {2. (-5) ]} =
↓
60 ÷ (-10) = -6
respondido por:
0
60÷{2. [-7+18÷(+9)]}
60÷{2. [-7+2]}
60÷{2. -5}
60÷ (-10)
= -6
.... Acho que está certo, espero ter ajudado!!!
60÷{2. [-7+2]}
60÷{2. -5}
60÷ (-10)
= -6
.... Acho que está certo, espero ter ajudado!!!
Perguntas similares
7 anos atrás
7 anos atrás
9 anos atrás
9 anos atrás
9 anos atrás
9 anos atrás